EKSPLORASI PENGALAMAN SISWA KELAS V DALAM MENGGUNAKAN GAME LITERASI BERBASIS QUIZIZZ PADA PROGRAM KAMPUS MENGAJAR ANGKATAN 8 DI SDN 48/I PANEROKAN - Pinta Uli Panjaitan; Mei Seven Panjaitan, Egi Amaza Mawaddah, Aulia Yunita Rosanti, Candra Rindi Irawan (CV. ADIBA ASIHA AMIRA, 2025)
The problem that occurs is the low motivation and literacy understanding of students' subject matter, which is caused by the lack of variation in the learning methods applied. This study aims to explore the experience of grade V students in using Quizizz-based literacy games in the 8th Batch Teaching Campus Program at SDN 48/I Penerokan. This study uses a qualitative approach with an exploratory method. Data collection techniques are carried out through observation, in-depth interviews with students, and analysis of quiz results carried out using Quizizz. The data obtained was analyzed descriptively to identify the student experience and the impact of using Quizizz on learning. The results of the study show that the use of Quizizz-based literacy games has a positive impact on the learning experience of grade V students at SDN 48/I Penerokan. This can be seen from the increase in motivation, material understanding, and student involvement in the learning process. In addition, the use of Quizizz also helps students in developing social skills and time management. This shows that interactive learning methods can be an effective solution to improve learning outcomes. While there are some challenges related to technology access and students' understanding of the use of Quizizz, the benefits obtained are much more significant. This research underscores the importance of innovation in education to create more engaging and meaningful learning experiences